A competição entre o etanol de segunda geração e a produção de eletricidade pelo uso do bagaço - Maluf, Gabriel (2014)
Brazil has excellent conditions for the development of bioenergy. Programs such as the ethanol attracts the world's attention by presenting an economical and ecological alternative to replace fossil fuels. New technologies for producing biofuels begin to show viable and production of second generation ethanol from the use of sugar cane bagasse, emerges as an important option in the energy matrix of the country. Also the generation of electricity from bagasse is a reality in alcohol and sugar mills, still having great possibility for expansion in the sugarcane industry. Thus there are two important economically viable and capable of growth that require the same input for its continuities technologies. However, it is not known whether there will be sufficient to meet the growth of both or if they will compete for biomass in the future and, in this case, how such competition will be. In recent years many studies investigating aspects related to biofuels of first and second generation, ethanol from corn, international markets of these products, the potential of biofuels byproducts, among others have been developed. However, were not considered neither in the technology of second generation ethanol production and electricity at the same time, both power from bagasse from sugar cane. This paper investigates the competition between the second-generation ethanol and bioelectricity production (cogeneration) by the common use of two technologies in Brazil, which is the pulp of sugar cane. To this end, we use a computable general equilibrium model known as Emissions Prediction and Policy Analysis - EPPA, able to design scenarios of growth of Brazilian and world economies, considering the production, consumption and international trade in different economic sectors, in particular in the agricultural and energy sectors. Are introduced in the modeling technological variables of sugar cane, such as cogeneration power plants using as an energy source bagasse and ethanol production technology of second generation bioenergy sectors. We also consider the possible evolution of ethanol demand in world markets, and the mandates for use of biofuels. The results indicate that there is considerable competition between the two technologies through the use of bagasse, with a predominance of the use of this feature, once plentiful, for the use of liquid fuels. As become more efficient production of second generation ethanol, greater competition for resources and lower the volume of available bagasse for cogeneration, and there may be a lack of raw material for the production of electricity in a more favorable scenario to the new technology. The development of second generation ethanol allows greater availability of land for other uses, since the higher productivity of this technology and the productivity gains of the first generation, allow to supply the demand for the product with less need for arable land. The second generation ethanol does not contribute significantly to increase the Brazilian demand for the product, however, the liberalization of international trade would bring high increase in production of both, first generation and the second generation ethanol, generating greater need for this growing areas order and also increase the generation of electricity from cogeneration, due to the increased availability of bagasse.